CORRELATIONS OF PHYSICAL-MECHANICAL PROPERTIES OF THE BOBONARO CLAY IN TIMOR, AND ITS IMPLICATIONS IN GEOTECHNICAL WORK: KORELASI DAN IMPLIKASI GEOTEKNIK TERHADAP SIFAT KUAT GESER LEMPUNG BOBONARO DI TIMOR - Adept Titu-Eki; Nugraha K. F. Dethan (INTAN Jurnal Penelitian Tambang, 2023)
Many geotechnical problems like slope failures and other infrastructure damage are common in civil and mining projects on the Bobonaro Clay Complex in Timor. Obtaining relevant geotechnical data for a complete engineering analysis is often time-consuming and expensive. Therefore, a study on the relationship between the parameters can be a powerful tool in these situations. Here we used multiple linear regression analysis to determine the correlation between the physical properties (clay content and plasticity index) and mechanical properties (angle of internal friction and cohesion) of the Bobonaro Clay. The data are 53 clay samples from Kupang, East Nusa Tenggara Province. These samples were from geotechnical drilling and Atterberg tests, grain size–hydrometer analysis, and unconsolidated–undrained Triaksial tests. Of all the correlation attempts, we found that only the clay content – plasticity index, and clay content – angle of internal friction exhibited a moderate correlation with a positive trend. The results of the multiple linear regression correlation also failed to express a good model; therefore, it was replaced by simple linear regression analysis. The various factors that need to be considered in a geotechnical correlation study, along with the significance and uniqueness of the Bobonaro clay, are also addressed in this article.